Tuned S‐Scheme Cu2S_TiO2_WO3 Heterostructure Photocatalyst toward S‐Metolachlor (S‐MCh) Herbicide Removal - Enesca, Alexandru; Isac, Luminita (Materials, 2021)
A dual S‐scheme Cu2S_TiO2_WO3 heterostructure was constructed by sol–gel method using a two‐step procedure. Due to the synthesis parameters and annealing treatment the hetero‐structure is characterized by sulfur deficit and oxygen excess allowing the passivation of oxygen vacancies. The photocatalytic activity was evaluated under UV and UV–Vis irradiation scenarios using S‐MCh as reference pollutant. The heterostructure is composed on orthorhombic Cu2S, anatase TiO2 and monoclinic WO3 with crystallite sizes varying from 65.2 Å for Cu2S to 97.1 Å for WO3. The heterostructure exhibit a dense morphology with pellets and particle‐like morphology closely combined in a relatively compact assembly. The surface elemental composition indicate that the heterostructure maintain a similar atomic ratio as established during the synthesis with a slight sulfur deficit due to the annealing treatments. The results indicate that the three‐component heterostructure have higher photocatalytic efficiency (61%) comparing with two‐component heterostructure or bare components. Moreover, Cu2S_TiO2_WO3 exhibit a superior constant rate (0.114s−1) due to the high concentration of photogenerated charge carriers, efficient charge separation and migration.
Keywords: herbicide; s‐metolachlor; wastewater; photocatalysis; semiconductors; S‐scheme mechanism